2016
DOI: 10.35790/ecl.4.1.2016.12480
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran NIHSS pada Pasien Stroke di Ruang Rawat Inap Neurologi RSUP Prof. Dr. R. D. Kandou Manado periode Juli 2014 - Juni 2015

Abstract: Stroke is the interruption of blood flow to the brain that occurs suddenly and persists for more than 24 hours, which can cause disability. NIHSS is a measurement tool assessing the outcomes of stroke. This study aimed to describe NIHSS in stroke patients in the Neurology Departement of Prof. Dr. R. D. Kandou Manado, for the period of July 2014 – June 2015. This is a descriptive retrospective study which used secondary data in the form of inpatients medical record. The result of this study showed that 136 stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…9 The above differences can be explained through research which examined the NIHSS score of ischemic stroke patients when entering and leaving treatment, it was found that the NIHSS score at admission was higher than at discharge. 21 In this study, there is a significant relationship between AIP and the NIHSS score with a p=0.017 (p<0.05) with a positive direction of correlation and a weak correlation strength of r=0.262. The direction of positive correlation means that the higher the AIP of ischemic stroke patients, the higher the NIHSS score.…”
Section: Resultsmentioning
confidence: 47%
“…9 The above differences can be explained through research which examined the NIHSS score of ischemic stroke patients when entering and leaving treatment, it was found that the NIHSS score at admission was higher than at discharge. 21 In this study, there is a significant relationship between AIP and the NIHSS score with a p=0.017 (p<0.05) with a positive direction of correlation and a weak correlation strength of r=0.262. The direction of positive correlation means that the higher the AIP of ischemic stroke patients, the higher the NIHSS score.…”
Section: Resultsmentioning
confidence: 47%
“…Prevalensi kasus stroke tertinggi terdapat di Sulawesi Utara (10,8%) dan terendah di Provinsi Papua (2,3%). 6 Di Kota Manado, khususnya di Instalasi Rehabilitasi medik RSUP Prof.…”
unclassified
“…R. D. Kandou, hemiparesis merupakan penyakit terbanyak tahun 2011 dengan 211 kasus baru dan sebagai urutan kedua terbanyak pada tahun 2013 dengan persentase 27% dari total kunjungan pasien, dan kembali menjadi penyakit terbanyak pada 2016 dengan 1.890 kasus. 6 Hemiparesis adalah sindrom klinis yang awal timbulnya mendadak, progesif cepat, berupa defisit neurologis fokal yang berlangsung 24 jam atau lebih atau langsung menimbulkan kematian, dan semata-mata disebabkan oleh gangguan peredaran darah otak non-traumatic. 7 Disfungsi motorik yang paling umum adalah hemiparesis karena lesi pada sisi otak yang berlawanan.…”
unclassified